Venous pressure during intravenous regional anesthesia: Implications for setting tourniquet pressure - Borzoo Farhang; Alex C Lesiak; Daniel J Ianno; Hayk Minasyan; Adam B Shafritz; Christopher M Viscomi (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Intravenous regional anesthesia (IVRA) is utilized for upper extremity surgery, but higher tourniquet pressure and longer inflation time increase the risk of soft tissue and nerve injury. We investigated the duration and magnitude of elevated venous pressure during IVRA to assess the possibility of safely lowering the tourniquet pressure during surgery. Material and Methods: Twenty adult patients scheduled for distal upper extremity surgery were enrolled. An additional intravenous catheter was placed in the surgical arm connected to a digital pressure transducer for monitoring venous pressure. Venous pressure was recorded prior to IVRA and every 30 s after injection of local anesthetic (LA) until the completion of surgery. Results: All 20 subjects completed the study without complication. Peak venous pressure was 340 mmHg in one patient which lasted for less than 30 s. Mean venous pressures fell below systolic blood pressure after 4.5 min in all cases except one. This patient had elevated venous pressures for 24 of 25 min of tourniquet time exceeding systolic blood pressure. The only statistically significant intraoperative factor associated with elevated venous pressure was elevated peak systolic pressure (P = 0.001). Conclusions: We found that the mean peak venous pressure was below systolic blood pressure in only 14 of the 20 subjects, and the peak injection pressure exceeded 300 mmHg in one patient. Another patient's venous pressure remained above systolic blood pressure for 24 of 25 min of tourniquet time. Current precautions to prevent LA toxicity may be insufficient in some patients and attempts to lower tourniquet pressures to just above systolic blood pressures soon after IVRA injection may result in toxicity, specifically if systolic pressure is elevated.